What Is the Level of Forensic Psychiatry Knowledge Among Psychiatrists in Turkey? "In Your Opinion, Should Forensic Psychiatry Be A Sub-Specialty?" - Saygılı, Çağatay; Ak, Sertaç; Cantürk, Gürol (The Bulletin of Legal Medicine, 2019)
Purpose:Even though the Forensic Psychiatry is currently defined as a sub-specialty of psychiatry in many countries, current regulations in Turkey does not provide such structured training. In this study, we aimed to evaluate the level of the knowledge of current registered mental health physicians practicing in our country, about forensic psychiatry and determine their point of view regarding forensic psychiatry to be a sub-specialty. Methods:The survey was distributed on March 2017 in an electronic mail group in which majority of psychiatrists as well as trainees are registered. Two hundred and seven (207) psychiatric physicians, working both in the public (State Hospital, Education and Research Hospital, University Hospital) (184 people), private hospitals (8 people) and private clinics (15 people) participated in the survey. As a means of data collection, "Demographic Information Questionnaire" and "Knowledge Level Questionnaire for Determining Knowledge Levels in Health Law of Psychiatrists" were employed which were compiled by the researchers. Results:The average scores, ranging between 1 and 5, in the Knowledge Level Questionnaire was determined to be 3,44. While 187 (90.3%) of the physicians participating in the survey thought that "Forensic Psychiatry" should be defined as a sub-specialty, 20 (9.7%) stated that it is not necessary. When gender, the current title of the physician, the Forensic Psychiatry Rotation, and the given answers to the 8thquestion were all checked, it was seen that, as the age increases, the demand for forensic psychiatry as a sub-specialty decreases significantly. Discussion:The average level of knowledge is unaffected by vocational experience, type ...